A novel three-dimensional visualization system revealed an essential adaptive angiogenic response during the early phase of pulmonary hypertension. (25th November 2020) - Fujiwara, T; Takeda, N; Hatano, M; Nishimura, S; Komuro, I
Abstract: Background: Pulmonary hypertension (PH) is characterized by increased pulmonary vascular resistance and right heart failure with progressive narrowing or occlusion of the pulmonary artery. However, the assessment of vascular remodeling is mostly limited to averaged increases in wall thickening, and even the role of vascular endothelial growth factor (VEGF), remains incompletely understood; Although abundantly expressed VEGF is expected to elicit angio-obliteration and the knockout of hypoxia inducible factor (HIF) prevents PH in mice, VEGF inhibitor Sugen exacerbates hypoxia (Hx)-induced PH model, which is referred to as VEGF paradox. Purpose: To analyze three-dimensional (3D) spatiotemporal changes of pulmonary microstructure and function, which reflect the disease activity and lead to resolve the paradox. Methods and results: We developed a novel 3D visualization system of microstructural networks in whole mouse organ with single-cell resolution, using combined tissue clearing technique called CUBIC and multiphoton excitation microscope. The system enabled the simultaneous 3D evaluation of microvascular structure, invaded macrophages and fibrosis with effective penetration of several mm (whole organ). Three-dimensional observations of PH mice models including Hx, Sugen/Hx, and human-like Alk1+/− hereditary PH models, revealed that not only inward (negative) microvessel remodeling with stenosis, but also marked elongation of microvascular ECs, was evident except Sugen/Hx model at the early phase, which had not been detected by 2D histological sections. Comparable transcriptome analysis revealed that PGC1α, which regulates HIF-independent VEGF expression and angiogenesis, plays an important role in the characteristic response for mitochondrial and microvascular maintenance. PGC1α was up-regulated in the early phage in Hx and Alk1+/− PH models with microvascular angiogenetic change, whereas Sugen/Hx-model did not increase PGC1α expression and did not show microvascular remodeling. Furthermore pulmonary ECs-specific PGC1α-deficient mice exacerbated Hx-PH model with decreased VEGF expression and microvessel density, and administration of Baicalin, a flavonoid enhancing PGC1α expression, ameliorated Hx-PH model with increased VEGF expression. Conclusions: The 3D visualization system disclosed an unexpected change of angiogenic microvascular structure in the early phage of PH, which is regulated by EC PGC1α. Microvascular angiogenesis which is induced by up-regulation in PGC1α -VEGF pathway is a crucial factor for compensation of PH in the early phase, which provides a potential novel therapeutic target for PH. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): JSJP